Interferon gamma rapidly induces in human monocytes a DNA-binding factor that recognizes the gamma response region within the promoter of the gene for the high-affinity Fc gamma receptor. - Wilson, K C (1992)
Interferon gamma (IFN-gamma) transcriptionally activates several early-response genes in monocytes that are important for the ultimate phenotype of the activated macrophage. One of these genes is the high-affinity Fc receptor for IgG (Fc gamma RI). Recently, Pearse et al. [Pearse, R.N., Feinman, R. & Ravetch, J. V. (1991) Proc. Natl. Acad. Sci. USA 88, 11305-11309] defined within the promoter region of the Fc gamma RI gene an element, the gamma response region, which was necessary for IFN-gamma-induced enhancement of Fc gamma RI. In this report we describe the induction by IFN-gamma of a DNA-binding factor, FcRF gamma (Fc gamma RI DNA-binding factor, IFN-gamma induced), that specifically recognizes the gamma response region element. Electrophoretic mobility shift assays (EMSAs) demonstrated the presence of FcRF gamma in human monocytes within 1 min after exposure to IFN-gamma. On EMSA, FcRF gamma consisted of two complexes termed FcRF gamma 1 and FcRF gamma 2. The nuclear concentration of FcRF gamma rapidly increased, peaked at 15 min, and then fell after 1-2 hr. Dose-response studies revealed (i) as little as 0.05 ng of IFN-gamma per ml induced FcRF gamma, (ii) maximum activation occurred at 1 ng/ml, and (iii) steady-state levels of Fc gamma RI mRNA closely paralleled that of FcRF gamma. Since FcRF gamma was activated in cells normally not expressing Fc gamma RI RNA, other regulatory mechanisms must control Fc gamma RI-restricted tissue expression. Activation of FcRF gamma by IFN-gamma was inhibited by pretreatment with 500 nM staurosporin and 25 microM phenyl arsine oxide. These data suggest that a kinase and possibly a phosphatase activity are required for IFN-gamma-induced signaling of FcRF gamma in monocytes.